Pulmonary Infection and Colonization with Nontuberculous Mycobacteria, Taiwan, 2000–2012 - Chien, Jung-Yien (Centers for Disease Control and Prevention, 2014)
We analyzed samples from 13,652 patients who had respiratory cultures positive for mycobacteria in Taiwan during 2000–2012 and found that 56.9% were positive for nontuberculous mycobacteria (NTM). Whereas annual prevalence of tuberculosis decreased during the study period, prevalence of NTM disease and colonization increased, particularly among older patients and male patients.